(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Systemic-onset juvenile idiopathic arthritis (sJIA) or Still’s disease is a chronic inflammatory disease of unknown etiology belongs to the group of Juvenile Idiopathic Arthritis. In contrast to other JIA patients in whom the joint disease usually overshadows the more general symptomatology, in Systemic-onset juvenile idiopathic arthritis (sJIA) extra-articular features such as spiking fever, hepatosplenomegaly, lymphadenopathy, rash, pleurisy, or pericarditis, and vasculopathy are most prominent. Thus the onset of disease can be vary nonspecific and may suggest bacterial or viral infection, malignancy or other rheumatic disease. As it is highly characterized by its extra-articular systemic illness features, in some ways, it resembles a fever of unknown origin. We present 2 cases of fever of unknown origin, initially presented with fever and other extra-articular features, without any arthritis, but after several months develops arthritis and finally diagnosed as Systemic-onset juvenile idiopathic arthritis (sJIA) or Still’s disease . Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 84-88